Ethnonyms of Old and Modern Kharkiv - Удовенко, Лідія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The article is devoted to problems of toponymy of the big city. The author analyzed the Kharkiv ethnonyms as the representatives of the urban toponymy in the period from the 19th to the 21th century. The author has defined the function of ethnonyms in the history of the city of Kharkov, discovered and described the features of the phenomenon, which investigation.